TINJAUAN TEORITIS ATAS PENGARUH MANAJEMEN LABA DAN TINGKAT DISCLOSURE TERHADAP BIAYA EKUITAS - Sihombing, Jenny (Jurnal Ekonomis, 2011)
Although the mechanism of the stock market perfectly fair may not be able to achieve it is caused by a conflict of interest and lack of transparency corporate issuers, but the improvement efforts are continued to be done to protect investors and for the credibility of the capital market itself. The purpose of this paper is to investigate the effect of earnings management on the cost of equity and influence the level of disclosure on the cost of equity, and to build research models associated with these variables through a review of the literature. The results show that earnings management has a positive effect on the Cost of Equity, Disclosure Level has significant effect on the Cost of Equity and Earnings Management negatively affect the level of disclosure of financial statements with a model that has been done. Keywords: Earning Management, Disclosure, Capital Asset Pricing Model, Cost of Equity